The intramolecular agonist is obligate for activation of glycoprotein hormone receptors. Issue 8 (10th July 2020) - Schulze, Annelie; Kleinau, Gunnar; Neumann, Susanne; Scheerer, Patrick; Schöneberg, Torsten; Brüser, Antje
Abstract: In contrast to most rhodopsin‐like G protein‐coupled receptors, the glycoprotein hormone receptors (GPHR) have a large extracellular N‐terminus for hormone binding. The hormones do not directly activate the transmembrane domain but mediate their action via a, thus, far only partially known T ethered A gonistic LI gand ( TALI ). The existence of such an intramolecular agonist was initially indicated by site‐directed mutation studies and activating peptides derived from the extracellular hinge region. It is still unknown precisely how TALI is involved in intramolecular signal transmission. We combined systematic mutagenesis studies at the luteinizing hormone receptor and the thyroid‐stimulating hormone receptor (TSHR), stimulation with a drug‐like agonist (E2) of the TSHR, and structural homology modeling to unravel the functional and structural properties defining the TALI region. Here, we report that TALI (a) is predisposed to constitutively activate GPHR, (b) can by itself rearrange GPHR into a fully active conformation, (c) stabilizes active GPHR conformation, and (d) is not involved in activation of the TSHR by E2. In the active state conformation, TALI forms specific interactions between the N‐terminus and the transmembrane domain. We show that stabilization of an active state is dependent on TALI, including activation by hormones and constitutively activating mutations.